2015
DOI: 10.1177/0883073815609151
|View full text |Cite
|
Sign up to set email alerts
|

Topographical Distribution of Epileptogenic Tubers in Patients With Tuberous Sclerosis Complex

Abstract: Tuberous sclerosis complex is a multisystem genetic syndrome often affecting the central nervous system. The purpose of the current study was to identify topographical patterns in the distribution specific to epileptogenic (n = 37) and nonepileptogenic (n = 544) tubers throughout the brain for a cohort of 23 tuberous sclerosis complex patients with a history of seizures. Tubers localized to the inferior parietal lobes, middle frontal lobes, middle temporal lobes, or central sulcus regions were associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Learning difficulties were associated with tuber load in the left hemisphere, mainly in the parietal but also in the temporal area-areas involved in language processing. This is consistent with previous studies (6,19,20) that showed associations of significantly high densities of tubers in the inferior parietal lobe and middle temporal lobe with lower IQ scores and learning difficulties. In our study, the somatosensory cortex function correlated with emotional regulation (21), whereas tubers in this location correlated with shyness and mood disorder.…”
Section: Discussionsupporting
confidence: 93%
“…Learning difficulties were associated with tuber load in the left hemisphere, mainly in the parietal but also in the temporal area-areas involved in language processing. This is consistent with previous studies (6,19,20) that showed associations of significantly high densities of tubers in the inferior parietal lobe and middle temporal lobe with lower IQ scores and learning difficulties. In our study, the somatosensory cortex function correlated with emotional regulation (21), whereas tubers in this location correlated with shyness and mood disorder.…”
Section: Discussionsupporting
confidence: 93%
“…Nonetheless, when no "stand out" tuber is found, distinguishing epileptogenic and non-epileptogenic lesions on anatomical MRI remains difficult. The large size of the tubers or their location [72,73], the presence of calcification and/or "cyst-like appearance [74], the specific aspect of the tuber center [45] have been suggested to be indicators of epileptogenicity but have not been shown to be adequately predictive of epileptogenicity in a pre-operative setting [69]. With the ongoing hypothesis that the malformed tissue surrounding the cortical tuber might be part (or even the core) of the epileptogenic zone, studies have suggested that careful identification of perituberal abnormalities might be more informative in choosing the right tuber or group of tubers for investigation and/or resection than the tubers themselves.…”
Section: Mri Datamentioning
confidence: 99%
“…Brain MRI is challenging in patients with TSC, and individual studies have focused on diverse features (size or localization, 38 presence of calcification and/or cyst‐like appearance, 39 tuber‐center characteristics 40 ), with each potentially associated with epileptogenicity. The strongest predictive factor of seizure freedom after surgery is the co‐occurrence within a single tuber of both bigger size and calcifications, 23,29 or without invasive recordings, a single, clear‐cut lesion 41 .…”
Section: Discussionmentioning
confidence: 99%